1982
DOI: 10.1055/s-2007-1022231
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Global Lung Function in Unilateral Fibrothorax after Conservative Therapy and Decortication

Abstract: Twenty-six patients suffering from unilateral fibrothorax were investigated before surgery or conservative therapy (decortication, n = 15; conservative treatment, n = 11) and followed up after 24.5 and 18.6 months respectively. Global lung function analysis was done by body plethysmography, ventilation and gas exchange analysis and blood-gas analysis under resting and exercise conditions. Regional lung function analysis included the semiquantitative description of fibrothorax by X-ray photos, and ventilation-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 3 publications
1
4
1
Order By: Relevance
“…Here it must be mentioned, however, that the values rose by a relatively moderate degree; in the best subgroup the average improved function was only 13.8 % above preoperative values. These results correlate with those of Petro and co-workers (6) . One the othe r hand, we could not identify any decrease in pulmonary functioning within the first 3 postoperative mont hs (Fig.…”
Section: As Deco Rtication Is a Relatively Ex Tensive Operation In In-supporting
confidence: 92%
“…Here it must be mentioned, however, that the values rose by a relatively moderate degree; in the best subgroup the average improved function was only 13.8 % above preoperative values. These results correlate with those of Petro and co-workers (6) . One the othe r hand, we could not identify any decrease in pulmonary functioning within the first 3 postoperative mont hs (Fig.…”
Section: As Deco Rtication Is a Relatively Ex Tensive Operation In In-supporting
confidence: 92%
“…In our series six patients had very low values for both VC and FEV1 and the majority did not reach the lowest reference value of FEV1 for a healthy population. Konietzko et al showed in his study that gradual improvement of FVC can be observed within two years after treatment for CPE [6,19]. Similarly to Toomes et al [8] and contrary to other series [7] we did not observe any influence of the time of decortication on the spirometric values.…”
Section: Discussioncontrasting
confidence: 57%
“…Earlier studies have shown arguably, that there is no significant improvement in the functional status (spirometry results) of chronic ET patients undergoing PD [7,8]. Recent studies have, however, supported the importance of PD as the cornerstone intervention in the effective management of chronic ET both in tuberculous and non-tuberculous patients [9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, studies have reported no improvement in functional outcomes in terms of spirometry for patients undergoing PD [7,8]. Recent studies have supported the importance of PD in terms of improvement of spirometric parameters in terms of forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%